2010
DOI: 10.1016/j.ejpain.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multimodal inpatient treatment for pediatric chronic pain: A comparison between children and adolescents

Abstract: Children display similar pain-characteristics to adolescents when entering inpatient treatment. A multimodal inpatient program appears to stop the the long-term vicious cycle of disability and pain for both children and adolescents. The demonstrated gender differences raise issues for further research and the possibility of additional pain management strategies for girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 46 publications
1
53
0
6
Order By: Relevance
“…23 The outcomes used in each trial for the respective domains are shown in Table 1. Due to overlapping samples, only data from children aged 7 to 10 y were included from Hechler et al 27 …”
Section: Measurement Domainsmentioning
confidence: 99%
“…23 The outcomes used in each trial for the respective domains are shown in Table 1. Due to overlapping samples, only data from children aged 7 to 10 y were included from Hechler et al 27 …”
Section: Measurement Domainsmentioning
confidence: 99%
“…Kasdien pildomas dienynas leidžia geriau suprasti vaiko skausmo pobūdį, dažnumą, intensyvumą. Jis ne tik padeda geresnei įtampos / migrenos tipo galvos skausmo diferenciacijai, tačiau kartu leidžia ir pačiam vaikui sustiprinti savikontrolės jausmą [47].…”
Section: Lėtinio Skausmo įVertinimasunclassified
“…Leider ist die Studienlage bezüglich der Wirksamkeit stationärer multimodaler schmerztherapeutischer Interventionen für Kinder mit chronischen Schmerzen sehr beschränkt. Hechler et al [13] konnten im Rahmen einer umfangreichen Literatursuche lediglich drei prospektive Langzeitstudien über stationäre Schmerztherapieprogramme für Kinder identifizieren, von denen zudem zwei Studien [6,15] lediglich vorläufige Auswertungen der vorliegenden Studie darstellen. Da auch diese bisherigen drei publizierten prospektiven Verlaufsstudien die Multidimensionalität chronischer Schmerzen entweder gar nicht [6,29] oder nur unzureichend [15] erfassen, hat die vorliegende prospektive Studie zwei Ziele:…”
Section: Langzeiterfolge Einer 3-wöchigen Stationären Schmerztherapieunclassified
“…In Anlehnung an Hechler et al [15] wird zudem postuliert, dass Kinder unter 11 Jahren im gleichen Ausmaß profitieren wie Kinder über 11 Jahren. schwer beeinträchtigenden chronischen Schmerzen eingeschlossen, die sich in der Schmerzambulanz des Vodafone Stiftungsinstituts und Lehrstuhls für Kinderschmerztherapie und Pädiatrische Pallia tivmedizin der Vestischen Kinderund Jugendklinik Datteln, Universität Witten/Herdecke (Vodafone Stiftungsinstitut), zwischen Januar 2004 und Januar 2007 vorstellten, die Einschlusskriterien erfüllten und einer Studienteilnahme zustimmten.…”
Section: Langzeiterfolge Einer 3-wöchigen Stationären Schmerztherapieunclassified
See 1 more Smart Citation